Agronomic biofortification of basmati rice (Oryza sativa L.) through iron and boron under varying seedling densities - Rajput, Pradeep; Singh, Adesh; Rajput, Ravindra Kumar; Bhatt, Rajan; Alamri, Saud; Kanaujiya, Pradeep Kr.; Gautam, Sandip Kumar (Frontiers in Sustainable Food Systems, 2024)
At present, we have adequate production of rice for fulfill the diet of humans, now it is time to produce biofortified rice, whose grains contain enough amounts of nutrients like iron and boron. Two field experiments were carried out in kharif 2019 and 2020 at Meerut, (U.P.) India, to find the effect of iron and boron nutrition on rice with different planting densities. The main plot treatment consists of three planting densities and sub plot treatment consisted of five foliar application of micronutrients were tested in a Split-Plot Design (SPD) with three replications.The results revealed that the rice transplanted with one seedling/hill gave the highest iron and boron content in grains and/or the crop fortified with iron and boron @ 0.1% and 0.04% applied at maximum tillering (MT) and panicle initiation (PI) stages of rice, respectively. The higher values of yield contributing characters vis., effective tillers/m 2 , panicle length (cm), grains weight/panicle (g) and test weight (g) and quality parameters vis., nutrient content in grain (mg/kg), volume expansion ratio, protein content in grains (%) and amylose content (%) of rice were noticed in one seedling/hill except effective tillers/m 2 during 1 st and 2 nd years. Application of Fe and B at MT and PI stages of rice had improved almost all the yield attributes and quality parameters. Planting density of two and three seedlings/hill recorded at par values of grain yield followed by one seedling/hill. Rice transplanted with three seedlings/hill obtained an average of 10.1 and 10.6% more grain yield than one seedling/hill during 1 st and 2 nd year, respectively.